Growing the knowledge base in evaluation : the contributions of J. Bradley Cousins - Chouinard, Jill Anne; Bourgeois, Isabelle, 1976-; Amo, Courtney (Evaluation and society., 2019)
"Evaluation use was identified by Henry and Mark (2003) as being the single most studied area in the field of evaluation. They refer with a sense of nostalgia to the 'golden age' of research on use perhaps almost implying that it came and went. Professor J. Bradley Cousins has had a longstanding and continuing commitment to advancing theory and practice regarding use through empirical research on evaluation, and through the professional development of students and practitioners within North America and internationally. The important influence and impact of the contributions of Cousins and associates is the focus of this edited book. This book brings together a distinguished, international group of authors, to reflect on the areas of contribution of Professor Cousins, and situate his work within contemporary areas of evaluation research and practice. Each chapter describes how the study and practice of evaluation has weaved its way through our understanding of organizational learning, participatory evaluation, and evaluation capacity building. The book concludes with a reflection by Professor Cousins himself on what these insights mean for the field of evaluation, and what future areas of research and contribution can be planned for and anticipated"--